Perlindungan Hukum terhadap Pemegang Hak Merek Dagang Batik â€œBulanâ€ Kota Pekalongan - Yustiana Dwirainaningsih; Mursidah Mursidah; Dheasari Rachdantia (Universitas Batanghari Jambi, 2023)
This study aims to analyze how legal protection is for trademarks that have been registered and what legal remedies have been taken by business actors and when. Batik is one of the intangible cultural heritages and the need for legal protection for trademarks that have been registered, one of which we take in this research is Batik Bulan, we are interested. A brand is one of the images as well as a good name for the company, it can be used as an identity for the goods it produces as an identifier and at the same time as a differentiator from other batik manufacturers. If there is no protection for a registered or well-known mark, a problem will arise, one of which will arise in relation to a dispute over the trademark. In this research method we use the normative juridical method, by examining the rules, norms, rules that greatly influence the problem to be studied. The results in this study indicate that every rule, principle that is carried out is in accordance with Law number 20 of 2006 concerning brands and geographical indicators as well as the reality on the ground to the problems that we will examine through one approach, namely through an empirical juridical approach, this approach aims to research This can be used with the aim of obtaining knowledge about the sociological aspects of society regarding the need to know about the legal protection of registered marks. For one of the well-known brands or registered legal protection through two events, namely preventive legal protection and repressive legal protection, this is done to protect entrepreneurs or trademark rights holders from acts against the law committed against registered brands, it is necessary to provide legal protection to trademark rights of registered goods. One of our research objects is Batik Bulan